2013
DOI: 10.3389/fpls.2013.00240
|View full text |Cite
|
Sign up to set email alerts
|

Minor loading vein acclimation for three Arabidopsis thaliana ecotypes in response to growth under different temperature and light regimes

Abstract: In light of the important role of foliar phloem as the nexus between energy acquisition through photosynthesis and distribution of the products of photosynthesis to the rest of the plant, as well as communication between the whole plant and its leaves, we examined whether foliar minor loading veins in three Arabidopsis thaliana ecotypes undergo acclimation to the growth environment. As a winter annual exhibiting higher rates of photosynthesis in response to cooler vs. warmer temperatures, this species might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
91
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(93 citation statements)
references
References 47 publications
2
91
0
Order By: Relevance
“…Decreased tocopherol levels at the end of the photoperiod and a lesser maximal NPQ capacity under experimental high-light exposure in the Italian ecotype suggest the possibility that this ecotype may be genetically programmed to allow a greater generation of redox-dependent signals, resulting from both less detoxification of ROS (via tocopherol) and less preemptive counteraction of ROS formation (via thermal dissipation). Future studies should explore the possibility that redoxdependent signaling networks provide input for genetic differences in leaf development in the Swedish versus the Italian ecotypes (Cohu et al 2013a, b;Adams et al 2014) and that a possible difference in the set-point of ROS formation (perhaps via differential expression of the NPQcontrolling PsbS protein, the protein S of photosystem II, required for rapidly reversible dissipation of excess absorbed light [Li et al 2009] and/or genes in tocopherol biosynthesis) between these two ecotypes may be one of the mechanisms of ecotypic adaptation to the environment.…”
Section: Interplay Between Chloroplast Modulators In the Context Of Lmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased tocopherol levels at the end of the photoperiod and a lesser maximal NPQ capacity under experimental high-light exposure in the Italian ecotype suggest the possibility that this ecotype may be genetically programmed to allow a greater generation of redox-dependent signals, resulting from both less detoxification of ROS (via tocopherol) and less preemptive counteraction of ROS formation (via thermal dissipation). Future studies should explore the possibility that redoxdependent signaling networks provide input for genetic differences in leaf development in the Swedish versus the Italian ecotypes (Cohu et al 2013a, b;Adams et al 2014) and that a possible difference in the set-point of ROS formation (perhaps via differential expression of the NPQcontrolling PsbS protein, the protein S of photosystem II, required for rapidly reversible dissipation of excess absorbed light [Li et al 2009] and/or genes in tocopherol biosynthesis) between these two ecotypes may be one of the mechanisms of ecotypic adaptation to the environment.…”
Section: Interplay Between Chloroplast Modulators In the Context Of Lmentioning
confidence: 99%
“…While leaves of both ecotypes exhibited a strong response to growth at low temperature under high light, consisting of a greater number of phloem cells per minor vein and record high rates of photosynthetic oxygen evolution (Cohu et al 2013a, b), the Swedish ecotype had even more numerous minor vein phloem cells (Cohu et al 2013a), more pronounced phloem parenchyma cell wall ingrowths (presumably providing for a greater number of phloem parenchyma cell membrane localized ATPases and sucrose-efflux transporters important for the active loading of sucrose into the sieve elements; Adams et al 2014), and higher photosynthetic capacities (Cohu et al 2013b;Adams et al 2014) compared to the Italian ecotype when both were grown under moderate light at low temperature. Moreover, these two ecotypes, and hundreds of inbred lines derived from these two parents, have been used to dissect genes underlying the control of flowering and others involved in fitness and potential trade-offs in fitness (Å gren et al 2013;Grillo et al 2013;Dittmar et al 2014;Oakley et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Only the Swedish ecotype responded to a decrease in growth temperature (without an increase in growth light intensity) with an increase in the size of the sieve tubes of the leaves' minor veins (figure 3; see also [80,81]). A combination of both low temperature and high light during plant growth was required to elicit a similar response in the Italian ecotype (figure 3; see also [80,81]). These findings suggest that the two ecotypes of this winter annual species do not differ in the principal ability to adjust leaf anatomy to cool growth temperature, but do differ in the intensity of cues required to elicit such a response.…”
Section: Adaptation To Contrasting Environmental Challenges With Respmentioning
confidence: 99%
“…These responses are featured in figures 1 and 2 as (increased, decreased or genetically limited) carbon export capacity (phloem loading/ sugar transport) and photosynthetic capacity. Firstly, it was shown that number and size of the cells loading sugars into the phloem's sugar-transporting sieve tubes as well as number and size of the sieve tubes are adjusted to growth temperature in the winter annual species Arabidopsis and spinach [79][80][81]. The characterized winter annuals typically germinate in the autumn, overwinter as rosettes, and complete their life cycle in the following spring.…”
Section: Adaptation To Contrasting Environmental Challenges With Respmentioning
confidence: 99%
See 1 more Smart Citation